IMPLEMENTATION OF PERSONAL PROVIDER AS A COMPLEX INTELLECTUAL CAPITAL OF DOMESTIC ENTERPRISES MACHINE-BUILDING INDUSTRY: INSTRUMENTATION OF IMPROVEMENT - Nahorniak , H.S. (The actual problems of regional economy development, 2018)
The article is devoted to the study of the content of staffing as a component of the intellectual capital of the enterprises of the domestic engineering industry, and the toolkit for its improvement is proposed. The development of a modern enterprise is ensured by the social interaction of its employees and the interaction of the enterprise with the environment is established. The exchange of subjective values of the workers allows to realize the labor potential of the enterprise to a large extent. In itself, the process of forming the intellectual capital of an enterprise represents organizational and managerial innovations, which are determined by the needs of innovation development in the production and technological sphere. The exchange of knowledge and skills of individuals in the process of interaction is one of the most important factors in the development of the national innovation system. A prerequisite for the modernization of the Ukrainian economy is to increase the effectiveness of innovation activities, which is largely determined by the ability of economic actors to use and generate new knowledge derived from the intellectual results obtained by productive relations with the external environment, which is interpreted as staffing, which is necessary component of intellectual capital. The assessment of this component of intellectual capital is an essential tool for efficient management of its quality in the interests of innovative development of machine-building enterprises and provides feedback in human-oriented management of innovation activities. In this regard, the development of tools for improving staffing as a component of intellectual capital is an urgent task that is of considerable scientific and practical importance. The content of the concept of "human resources provision as a component of intellectual capital" is specified, the author's interpretation of the concept of "staffing as an integral part of the intellectual capital of machine-building enterprises" is given. The issue of management of human resources provision as a component of intellectual capital of domestic enterprises of mechanical engineering is disclosed. There are a number of problems that directly influence the growth of intellectual capital in Ukraine's machine-building industry. The toolkit for the development of the machine-building industry is presented at the expense of improvement of human resources provision as a component of intellectual capital. A model of intellectual capital is defined which can be interpreted using three main components: human capital (contains such component as staffing); organizational capital (corporate information systems, databases, hardware and software, organizational structures, patents, know-how, licenses, trademarks, corporate culture); consumer capital (the capital of relations, representing the causal mechanism of interaction of the company with consumers, suppliers, competitors, as well as the socio-economic potential of its brands, brands, image and reputation). It is noted that in a generalized way, the structure of personnel supply represents four interacting components: moral values (moral and cultural levels); creative abilities (including creativity); education (knowledge gained during the learning process); professionalism (work experience taking into account the performed work tasks).